2011
DOI: 10.2214/ajr.10.5618
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Comparison of Standard Didactic Lecture Versus High-Fidelity Simulation for Radiology Resident Contrast Reaction Management Training

Abstract: When compared with didactic lecture, high-fidelity simulation-based training of contrast reaction management shows equal results on written test scores but improved performance during a high-fidelity severe contrast reaction simulation scenario.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 26 publications
1
37
0
Order By: Relevance
“…More research is necessary to determine if different teaching methods result in different levels of comfort and skill with actual patient care. 3 Another study showed better immediate recall of material with slide-based lecture when compared to simulation.…”
Section: Discussionmentioning
confidence: 99%
“…More research is necessary to determine if different teaching methods result in different levels of comfort and skill with actual patient care. 3 Another study showed better immediate recall of material with slide-based lecture when compared to simulation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore in a study among Radiology trainees, Wang et al 23 demonstrated no significant improvement in written test scores among trainees receiving didactic lecture versus simulation based training in management of contrast reaction, but performance among simulation based training was superior when tested in contrast reaction simulation scenario. Our study reported a significantly improved performance in post-teaching MCQ from baseline in simulation group compared to those who received didactic lecture (18.80±1.40 vs 15.40±1.35).…”
Section: Resultsmentioning
confidence: 97%
“…The use of a control group that received no additional training was based on previous studies [21][22][23][24][25][26][27] also on the acquisition of technical skills (training group versus notraining group, didactic training alone, no additional intervention, or learned independently from a prepared text). The adoption of faculty-directed learning was based on the study 28 that showed that this form of teaching is superior to self-directed learning.…”
Section: Discussionmentioning
confidence: 99%